SOCIAL SCIENCES IN UZBEKISTAN DURING THE SECOND WORLD WAR: ANALYSIS OF SCIENTIFIC RESEARCH (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
During the war years, science and research activities in Uzbekistan were intensively continued. Educational institutions and research institutes relocated as a result of the evacuation made a significant contribution to the development of science in the republic. Despite the fact that it was a time of war, the rapid and positive reforms that were implemented stimulated development in the field of social sciences as well as in all branches of science. The establishment of the Academy of Sciences in the republic served to increase this process more consistently